Relação entre a concentração plasmática do peptídeo natriurético tipo b, índice cardiofemoral e equilíbrio ácido-básico em fetos de gestantes isoimunizadas - Ana Luiza Penido Ferreira (2008)
Introduction: Fetal anemia is a common result of alloimunization and is an important cause of fetal congestive heart failure resulting in heart dilation. Fetuses suspected of having heart failure present a higher cardiofemoral index and an increase in plasma BNP levels, because the cardiac hormonal system is activated by increased heart wall stretch due to increased left ventricular volume and pressure overload. Objective: The purpose of this study was to assess whether plasma concentration of BNP in fetuses with Rh isoimmunization is related to Cardio Femoral Index and whether BNP levels would correlate with ICF and bloodgases in fetal anemia. Patients and methods: 33 pregnant women were studied (22-31 weeks gestation at the first cordocentesis) referred for intrauterine fetal transfusion due to severe red blood cells isoimmunization. Up to 6 h prior to each cordocentesis, all fetuses were submitted to ultrasonography measurements where the Cardiofemoral Index was calculated. Samples of blood from the umbilical vein were collected for hemoglobin concentration and blood gas measurements. Plasma levels of BNP were determined with the use of plasma that had previously been frozen and thawed once. Plasma BNP was measured byradioimmunoassay. Pearsons correlation test and simple and multiple regression analysis were used to determine the association between the plasma concentration of BNP, the Cardiofemoral Index. Regression analysis was used to evaluate the relation between BNP and blood gases of the anemic fetuses with RH alloimmunization and BNP , ICF and some parameters of blood gases (HCO3 , pH and BE). Results: Anemia was severe in 17 (50%) fetuses, mild in 9 (26.47%) and in 8 patients (23.53%) the fetuses were not anemic; hemoglobin ranged from3.10 to 15.70 g/dL. The cardiofemoral index ranged from 0.43 to 0.87 and it was altered (>/=0.59) in 23 fetuses. A significant positive correlation was observed between BNP plasma fetal concentration and Cardiofemoral Index (Pearson r = 0.61, P < 0.0001). Simple regression analysis found a significant association between BNP and HCO3 , pH and BE (p<0,0001 for HCO3 ,and pH, p= 0,02 for BE) A multiple regression analysis showed a significant relation between BNP, ICF andthe same blood gases. (R2 =79,5%, 49,6%,43,2% respectively). Conclusions: These results suggest that fetal plasma concentration of BNP may increase in fetuses with heart dilation leading to a positive association between Cardiofemoral Index and plasma concentration of BNP. BNP is increased in fetal acidosis due to severe fetal anemia. The increase of BNP in fetal acidosis and cardiac heart failure, suggests that this cardiac hormone is secreted by the same mechanism of the adult.